Ten steps or climbing a mountain: A study of Australian health professionals' perceptions of implementing the baby friendly health initiative to protect, promote and support breastfeeding - Sheehan Athena; Gribble Karleen; Schmied Virginia; Taylor Christine; Dykes Fiona C (BMC, 2011)
Abstract Background The Baby Friendly Hospital (Health) Initiative (BFHI) is a global initiative aimed at protecting, promoting and supporting breastfeeding and is based on the ten steps to successful breastfeeding. Worldwide, over 20,000 health facilities have attained BFHI accreditation but only 77 Australian hospitals (approximately 23%) have received accreditation. Few studies have investigated the factors that facilitate or hinder implementation of BFHI but it is acknowledged this is a major undertaking requiring strategic planning and change management throughout an institution. This paper examines the perceptions of BFHI held by midwives and nurses working in one Area Health Service in NSW, Australia. Methods The study used an interpretive, qualitative approach. A total of 132 health professionals, working across four maternity units, two neonatal intensive care units and related community services, participated in 10 focus groups. Data were analysed using thematic analysis. Results Three main themes were identified: 'Belief and Commitment'; 'Interpreting BFHI' and 'Climbing a Mountain'. Participants considered the BFHI implementation a high priority; an essential set of practices that would have positive benefits for babies and mothers both locally and globally as well as for health professionals. It was considered achievable but would take commitment and hard work to overcome the numerous challenges including a number of organisational constraints. There were, however, differing interpretations of what was required to attain BFHI accreditation with the potential that misinterpretation could hinder implementation. A model described by Greenhalgh and colleagues on adoption of innovation is drawn on to interpret the findings. Conclusion Despite strong support for BFHI, the principles of this global strategy are interpreted differently by health professionals and further education and accurate information is required. It may be that the current processes used to disseminate and implement BFHI need to be reviewed. The findings suggest that there is a contradiction between the broad philosophical stance and best practice approach of this global strategy and the tendency for health professionals to focus on the ten steps as a set of tasks or a checklist to be accomplished. The perceived procedural approach to implementation may be contributing to lower rates of breastfeeding continuation.